Effects of Nicotine on Reaction Time among Albino Rats - Jackson Iheukwumere Osuh; Zainab Olamiku Onilenla; Emmanuel Etim Uye (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
Nicotine, a primary addictive compound in tobacco, is known to impact cognitive functions, including reaction time. While studies have been conducted on human subjects, animal models, such as Albino rats, provide valuable insights into the neurobehavioral effects of Nicotine. This study investigated the effects of Nicotine on reaction time in Albino rats. A factorial design was employed, involving a sample size of 20 Albino rats randomly assigned into four groups: two experimental groups and two control groups, with each group comprising male and female rats. The experimental groups were administered 5 mg of Nicotine solution, while the control groups received distilled water. Reaction time data were collected by placing each rat in a T-maze, with a food reward (mouse cube) positioned on a path for the rats to see and move toward. The data were analyzed using factorial ANOVA and independent samples t-test. Two hypotheses were tested and accepted at a significance level of p = 0.001. The results indicated that Nicotine significantly reduced reaction times in the experimental groups compared to the control groups. Additionally, the findings revealed that female Albino rats exhibited longer reaction times than male Albino rats. The study concludes that Nicotine influences the physiological, behavioral, and cognitive functions of both male and female Albino rats. It is recommended that the government and health sector stakeholders intensify efforts to inform and educate the public on the health risks associated with the continuous consumption of Nicotine-containing products.